2004
DOI: 10.1101/gad.1256504
|View full text |Cite
|
Sign up to set email alerts
|

Living with or without cyclins and cyclin-dependent kinases

Abstract: Entry into, progression through, and exit from the G1 phase of the mammalian cell cycle in response to extracellular mitogenic cues are presumed to be governed by cyclin-dependent kinases (Cdks) regulated by the D-type and E-type cyclins. Studies performed over more than a decade have supported the view that these holoenzymes are important, if not required, for these processes. However, recent experiments in which the genes encoding all three D-type cyclins, the two E-type cyclins, cyclin Ddependent Cdk4 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
896
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 977 publications
(920 citation statements)
references
References 111 publications
18
896
1
5
Order By: Relevance
“…These steps are frequently deregulated in malignant cells and are therefore potential targets for cancer intervening drugs (Vermeulen et al, 2003). However, recent findings suggested a high functional redundancy of the G1-S regulatory components, like CDK4 and CDK2 (Berthet et al, 2003;Ortega et al, 2003;Tetsu and McCormick, 2003;Malumbres et al, 2004;Sherr and Roberts, 2004). This new insight raises the need for identification of new regulators of the G1-S transition phase.…”
Section: Discussionmentioning
confidence: 99%
“…These steps are frequently deregulated in malignant cells and are therefore potential targets for cancer intervening drugs (Vermeulen et al, 2003). However, recent findings suggested a high functional redundancy of the G1-S regulatory components, like CDK4 and CDK2 (Berthet et al, 2003;Ortega et al, 2003;Tetsu and McCormick, 2003;Malumbres et al, 2004;Sherr and Roberts, 2004). This new insight raises the need for identification of new regulators of the G1-S transition phase.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin/Cdk complexes are themselves negatively regulated by Cdk inhibitors such as p16 INK4A , p21 CIP1 and p27 KIP1 (Sherr and Roberts, 2004). Whilst phosphorylation is recognized as a post-translational modification that significantly influences pRb activity, it is now apparent that other types of modification can also impact upon pRb/E2F.…”
Section: Introductionmentioning
confidence: 99%
“…Toward this end, we and others have shown that as part of its proproliferative program, androgen induces accumulation of Dtype cyclins (Knudsen et al, 1998;Xu et al, 2006). This class of cyclins interact with and activate cyclin-dependent kinases (CDK) 4/6 to promote G 1 progression during the cell cycle (Mittnacht, 1998;Sherr and Roberts, 2004). Recent studies have shown that AR stimulates cell cycle progression at least in part through induction of mTOR (mammalian Target of Rapamycin) activity, which facilitates cyclin D protein accumulation .…”
mentioning
confidence: 99%
“…Furthermore, p21 Cip1 protein levels are induced by androgen stimulation (Knudsen et al, 1998) and p21 Cip1 has been shown to be a direct AR target gene (Lu et al, 1999). Displacement of p21 Cip1 from active cyclin D1/CDK4 complexes allows p21 Cip1 to bind and inhibit CDK2 activity, thereby inhibiting progression through G 1 and into S phase (Sherr and Roberts, 2004). Thus, the ability of cyclin D1 to interact with p21 Cip1 is thought to be a critical function in promoting cellular proliferation and is often associated with mitogenic stimulation (Alt et al, 2002).…”
mentioning
confidence: 99%